Cox maze IV versus left atrial reduction for atrial contraction restoration. (June 2019) - Firmansyah, Dena K; Soesanto, Amiliana M; Hanafy, Dicky A; Bono, Arinto
Background: The Cox maze procedure is the gold-standard concomitant surgical procedure to restore sinus rhythm in rheumatic mitral valve disease with atrial fibrillation. Left atrial reduction surgery was found to be beneficial for rhythm conversion, but no study has investigated its efficacy compared to the Cox maze procedure for atrial contractility restoration. We aimed to compare the early success rate of left atrial contractility restoration with the Cox maze procedure and left atrial reduction in rheumatic subjects. Methods: Preoperative and within one-month postoperative electrocardiograms and echocardiograms of patients who underwent a Cox maze IV procedure or left atrial reduction with mitral valve surgery were compared. Effective atrial contraction was defined as A wave peak velocity ≥10 cm·s −1 or atrial filling fraction ≥20%. Results: Ninety patients (mean age 40.6 ± 10.2 years, 66.7% female) were divided equally into group A (Cox maze IV) and group B (left atrial reduction). The early sinus rhythm conversion rate was 64.4% versus 24.4% ( p < 0.001) in groups A and B, respectively. In patients with restored sinus rhythm, contractility was restored in 41.4% and 36.4% ( p = 1.000). Postoperative left atrial volume index ≤76 mL·m −2 was an independent variable associated with early atrial contractility restoration in both groups (prevalence rate 0.97, p = 0.007). Conclusions: In rheumatic subjects, the early sinus rhythm conversion rate was significantly higher after Cox maze IV compared to left atrial reduction, but for restoring left atrial contractility, left atrial reduction was not inferior to Cox maze IV.